Pilot Study: A Review of Personnel Involved in School Vision Screening and the Training Module in Betong, Malaysia - AB, Nurul Farhana; AH, Chen; MN, Abdul Rahim; PP, Goh (IIUM Medical Journal Malaysia, 2012)
Introduction: School vision screening program is a scheduled program under the Ministry of Health, Malaysia for 7, 12 and 15 years-old children in the government schools. The aim of this study was to review the school vision screening program from the perspective of the personnel involved as the screener. Methods: The evaluation of the performance of the screener was based upon the accurate referrals’ outcome from the school health database of Betong Division in Sarawak, Malaysia in the year of 2008. Results: The total accuracy of the referrals was 50.7%. Lower accuracy of the referrals was found significantly associated with Grade 1 [χ2 (2.N=304) = 28.810, p<0.001, OR 4.472, CI.95= 0.843=2.335] and among Native Iban [χ2 (2.N=304) = 7.901, p<0.05, OR 1.502, CI.95= 0.935=2.414]. Conclusions: Further review on the training modules demanded improvement and enhancement to suggest that training module might be one of the contributing factors on the performance of the screener.